Interfacial Synthesis of an Electro-Functional 2D Bis(terpyridine)copper(II) Polymer Nanosheet - Kenji Takada; Joe Komeda; Hiroaki Maeda; Naoya Fukui; Hiroyasu Masunaga; Sono Sasaki; Hiroshi Nishihara (Molecules)
Coordination polymers are attractive materials for various fields of practical application. The high degree of freedom of choice of metal ions and organic ligands plays a critical role in functional diversification. In the present study, we report the liquid–liquid interfacial synthesis of a 2D bis(terpyridine)copper(II) polymer thin film, Cu-tpy. The synthesized Cu-tpy was characterized by various microscopic observations such as TEM, SEM, and AFM, and spectroscopic measurements such as XPS, Raman spectroscopy, SEM/EDS, and UV–Vis spectroscopy. Synchrotron-radiated X-ray scattering confirmed that Cu-tpy was oriented crystalline films. Moreover, Cu-tpy showed electrochemical micro-supercapacitor behavior in the solid-state owing to its ionic nature. This study expands the potential of bis(terpyridine)metal(II) polymers as electro-functional materials.